Differentiated thyroid carcinoma: presentation and follow-up in children and adolescents - Papendieck, Patricia (2011)
To review our Pediatric Endocrinology Division ’ s experience with differentiated thyroid carcinoma (DTC) we analyzed retrospectively the records of patients with DTC that had been seen between June 1988 and June 2008. Results: Forty-fi ve patients (median age 13.7 years, 36 female) were diagnosed (papillary: 40, follicular: 5) with DTC presenting as a solitary nodule (n: 25), thyroid nodule with cervical adenopathy (n: 9) and multinodular goiter (n: 11). All underwent total thyroidectomy with resection of suspicious cervical lymph nodes (CLN). DTC was multicentric in 59 % and revealed extrathyroidal extension in 44 % . Initially, 44 % had CLN metastases and 24 % distant metastases. All patients underwent thyroid remnant ablation with 131 I and suppressive treatment. Median follow-up was 5.1 years with a diseasefree survival rate at 5 years of follow-up of 75 % . Eleven percent presented recurrences. Conclusion: Pediatric DTC has an aggressive behavior at presentation. Higher preoperative TSH levels were signifi - cantly associated with a more advanced disease at diagnosis. CLT was present concomitantly in a quarter of the patients and further studies are needed to establish differences in these patients ’ outcome. Diagnostic approach, total thyroidectomy, 131 I treatment and thyrotropin suppression allowed a good progression-free survival rate.